Iridium-catalyzed intramolecular asymmetric allylic etherification of salicylic acid derivatives with chiral-bridged biphenyl phosphoramidite ligands. Issue 16 (18th June 2021) - Pan, Bendu; Ouyang, Jia-Sheng; Zhang, Yaqi; Liang, Hao; Ni, Qiang; Chen, Bin; Pu, Xiaoyun; Jiang, Long; Cao, Rihui; Qiu, Liqin
Abstract : Iridium-catalyzed intramolecular asymmetric allylic etherification of salicylic acid derivatives was successfully realized for the first time. Abstract : Iridium-catalyzed intramolecular asymmetric allylic etherification of salicylic acid derivatives was successfully realized for the first time. By using chiral-bridged biphenyl phosphoramidite ligand L7, a class of novel chiral 1, 4-benzoxazepinones was prepared conveniently with good to excellent yields (up to 99%) and high enantioselectivities (up to 99% ee). The effect of different substituents on the enantioselectivity was also discussed. Compared with BINOL or biphenol-derived counterparts, catalysis with ligand L7 has obvious advantages in terms of catalytic activity and enantioselectivity. Mild conditions and a wide substrate scope demonstrate the practicability of this method. It was also found that the configuration of the product was directly related to the configuration of the alkene substrate and the E -substrate is more suitable for this reaction to obtain better enantioselectivity.